2009
DOI: 10.1080/09540120902814361
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and concurrent sexual relationships – a qualitative study among men in an urban South African community

Abstract: The aim was to explore and describe characteristics of males' social and sexual networks in a South African peri-urban community. Twenty in-depth interviews were conducted with men participating in a larger quantitative study where the median age of the men was 28.7 years and almost 56% had some high-school education, 17.2% were unemployed and 94.7% were not married. A Thematic Question Guide with open-ended questions was used for the interviews. A thematic content analysis was conducted to explore the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
5
25
1
Order By: Relevance
“…Second, the weights are dependent on the degree to which men would have knowledge of their peers' sexual behaviours. Although the validity of this assumption is unknown, qualitative interviews with some of the men found that they socialised in close-knit friendship groups [45]. In these circumstances it is likely that the sexual behaviour of their friends may well have been known.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the weights are dependent on the degree to which men would have knowledge of their peers' sexual behaviours. Although the validity of this assumption is unknown, qualitative interviews with some of the men found that they socialised in close-knit friendship groups [45]. In these circumstances it is likely that the sexual behaviour of their friends may well have been known.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the sampling weights used in the analysis are dependent on the degree to which men would have knowledge of their peers' sexual behaviours. Although the validity of this assumption is unknown, qualitative interviews with some of the men found that they socialised in close-knit friendship groups [32]. In these circumstances it is likely that the sexual behaviour of their friends may well have been known.…”
Section: Limitationsmentioning
confidence: 98%
“…As elaborated earlier, the pressures on men to be sexually active and prove their sexual prowess through multiple partners have been increasingly documented. For example, a recent South African study among urban men found that having concurrent sexual relationships was regarded as increasing their status as a man (Ragnarsson, Townsend, Thorson, Chopra & Ekström 2009). This perception has also been documented in studies with local youth (Anderson 2010;Lindegger & Maxwell 2007;Ratele, Fouten, Shefer, Strebel, Shabalala & Buikema 2007).…”
Section: Discussionmentioning
confidence: 99%